DD and PTV as victims of media globalisation. Issue 1 (2nd January 2017) - Sulehria, Farooq
ABSTRACT: Mainstream discourses on the globalisation of media that delineate the emergence of privately owned television channels in the periphery country as evening out metropolitan domination are belied by concrete evidence. This essay argues that the rise of southern players has undermined state broadcasting rather than dismantling 'media imperialism'. Based on two case studies, Pakistan Television (PTV) and Doordarshan (DD), this study demonstrates that the actual, if inadvertent, victim of globalisation has been state broadcasting and an associated developmentist model of television. As a result the decline of state-led television channels has radically transformed television systems in India and Pakistan. While DD and PTV view their audiences as citizens, the globalisation of media has resulted in a commodification of television audiences. Instead of public interest, audience maximisation has become the dominant logic of television systems in both these countries. In the process, developmentist television systems have been replaced by the commercially driven systems.